Behavior of Polish consumers on the financial market in the light of research results in the Central and Eastern Europe - Гембскі, Л.; Другов, О.; Gębski, Ł.; Druhov, O. (Видавництво Львівської політехніки, 2024)
Вміння правильно розуміти і користуватись фінансовими послугами вже є невідʼ ємною частиною знань дорослої людини. Мета статті - аналіз ринкової поведінки та знань споживачів на фінансовому ринку у світлі наукових досягнень та власних досліджень. Автори досліджують фактичний рівень фінансових знань польських споживачів та аналізують помилки споживачів. У статті автори зробили огляд літератури та найважливіших досліджень фінансових знань та поведінки споживачів на фінансовому ринку в Польщі та Україні – у контексті загально- європейського дослідження OECD/INFE. У статті також застосовано статистичний аналіз для визначення рівня фінансової грамотності на поведінку споживачів на фінансовому ринку.

Purpose – Financial literacy plays an increasingly important role in the formation of vital skills of the population. The ability to correctly understand and use financial services is already an integral part of the knowledge of an adult. Because of this, measuring the level of financial literacy plays an important social role. The aim of this article is to analyze market behavior and consumer knowledge on the financial market in the light of scientific achievements and own research. The authors examine the actual level of financial knowledge of Polish consumers and analyze the mistakes made by consumers. Design/methodology/approach – In the article, the authors reviewed the literature and the most important studies on financial knowledge and consumer behavior in the financial market in Poland and Ukraine – in the context of the pan-European OECD/INFE study. Then, the authors presented their own study of Polish consumers. The results of the survey conducted on a representative group of consumers were subjected to statistical analysis to detect relationships and correlations. Pearson’s χ2 non-parametric test was used to examine the relationship between two variables measured on a qualitative scale. The strength of the relationship is calculated based on Cramer’s V coefficient. The study conducted by the authors allowed them to formulate conclusions. Findings – Hypotheses were formulated regarding consumer behavior on the financial market. They were examined and confirmed by the results of the study. Consumers tend to overestimate their own financial competence and knowledge in this area. They also remain uncritical towards their mistakes. They also succumb to behavioral cognitive errors. As a result, decisions and choices made on the financial market are not always rational. Practical implications – The results of these studies are interesting for people and bodies responsible for consumer protection on the financial market. The awareness of the low – actual – level of knowledge and the tendency to make cognitive errors put in a new light the foundations of the policy in the field of institutional consumer protection (the postulate of increasing the level of protection) and the assessment of the economic education system (it is insufficient) Originality/value – This article presents new and unique results of a survey of a representative group of consumers. The survey was one of the first – on a European scale – to aim not only to collect consumers’ declarations regarding their financial knowledge, but also to critically verify the answers obtained.
Поведінка польських споживачів на фінансовому ринку у світлі результатів досліджень у Центральній та Східній Європі
Keywords: поведінка споживачів; захист прав споживачів; фінансова грамотність; економічна освіта; Consumer behaviors; Consumer protection; Financial literacy; Economic education; G51; G53; G40; I29; 336; 330.16; 316.422